PEMBINAAN DAN PENDAMPINGAN KOPERASI DALAM PENYUSUNAN LAPORAN KEUANGAN KOPERASI NASARI RAJA DAPOTAN KABUPATEN SAMOSIR - Djuli Sjafei Purba; Elfina O P Damanik; Wico Jontarudi Tarigan; Sri Martina; Tuahman Sipayung; Rosita Manawari Girsang; Liharman Saragih; Mahaitin H Sinaga (Universitas, 2024)
Financial statements are crucial in conducting business. The problem faced by the Nasari Raja Dapotan Corporation, which has an undertaking to sell pine rubber, located in the Hutaginjang village of Simanindo district of Samosir, is its inability to compile financial reports. It's because there are still limited human resources. The implementation of the commitment to the society is divided into three stages: the first stage is the observation stage, the second stage is education and material delivery and the third stage is support and evaluation. Results of implementation of commitment to the society on training preparation of Co-operation Financial Report conducted by the lecturer of the Faculty of Economics University of Simalungun and students of the faculty of economics USI went smoothly. With the hope of improving his knowledge of the importance of financial statements in accordance with the Financial Accounting Standards (FAS) because the benefits of complete and correct financial statement can improve financial management and improve the financial performance of the Nasari Raja Dapoton Corporation group.